Utilization Strategy of Discharged Seawater from Power Plant Cooling System to Reduce Energy Consumption: A Process Engineering Approach - Amaral, Clizardo; Yandri, Erkata; Ludji, Omrie; Sidharta, Rendy; Timba, Ayub; Ariati, Ratna (Heca Sentra Analitika, 2025)
Steam power plants are among the primary sources of electricity generation; however, they face significant challenges in terms of energy efficiency and environmental impact due to their high consumption of coal. Innovative strategies are required to reduce emissions and improve system efficiency. One potential approach is the reutilization of condenser cooling water to drive a hydropower turbine before being discharged into the sea. By harnessing the head and flow rate of this water, the kinetic energy from the waste stream can be converted into additional electricity. This study examines a process engineering approach to integrating a hydropower generation system with a steam power plant, encompassing technical analysis, energy efficiency, as well as economic and environmental impacts. Simulation results indicate that the system is capable of generating between 14.2 and 49.5 kW of power, depending on operating conditions and water availability. The electricity produced can be utilized for internal Steam power plant needs, such as cooling pumps and lighting, thereby reducing dependence on coal combustion. This strategy not only improves energy efficiency and reduces operational costs but also supports environmental conservation and the long-term sustainability of power plant operations.